Transfer of 3D Scanning Technologies Into the Field of Criminal Proceedings - Blahuta, R.I.; Blikhar, V.S.; Dufeniuk, O.M. (Science and Innovation, 2024)
Introduction. Everyday, hundreds ideas of innovative technologies are developed, and thousands innovative products and services are implemented. The practice of criminal proceedings does not stand aside these processes. In recent years, foreign specialists have been increasingly focusing on 3D scanning technologies and the potential of their use in investigations. Problem Statement. The problem of 3D technologies in the criminalistic practice has not been sufficiently developed in Ukrainian science, and the idea of using 3D technologies for fixing evidence, as well as tracing the evidence and corpus delicti is only at the initial stage of development. In the future, focus on active implementation of 3D scanning technologies in forensic activities is expected to increase. Purpose. On the basis of generalization of international experience, a systematic review of the advantages of using 3D scanning technologies in criminal proceedings has been carried out, and the prospects for the transfer of these innovations to the criminalistic practice in Ukraine have been outlined. Materials and Methods. Comparative analysis, formal and logical methods. Results. The use of 3D scanning technologies is a unique way of fixing the information about a criminal offense, which provides access to the virtual image of the crime scene for all participants of the criminal process. An investigator, a prosecutor, a judge, and a juror can visualize the crime scene using 3D model. The advantages of this process are universality, portability, agility, ease of use, efficiency, safety, multi-functionality, and cost effectiveness. Conclusions. The world practice of police services has proved the expediency of using laser scanning while investigating criminal offenses. Ukraine is also expected to make a progress in the technological support of police and expert services, insofar as effective counteraction to modern crimes without innovations is an impossible mission.